Історичний аспект становлення поняття “цінність” - Тимощук, Ганна (Видавництво Львівської політехніки, 2012)
Статья посвящена исследованию проблемы определения понятия “ценность”, в связи с этим рассматриваются основные исторические подходы к его пониманию. Подчеркнута важность изложенных трактовок для современных наук. The article studies the problem of the definition of “value”. In this connection the primary historical approaches of the concept’s understanding are considered. The author underlines the importance of stated interpretations for modern sciences.
Исторический аспект становления понятия “ценность”
Historical aspect of the formation of the concept of “value”
Keywords: ценность; особенности ценностей; формы существования ценностей; value; peculiarities of values; forms of values’ existence